2020
DOI: 10.1111/dom.14198
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of polyethylene glycol loxenatide monotherapy in type 2 diabetes patients: A multicentre, randomized, double‐blind, placebo‐controlled phase 3a clinical trial

Abstract: Aim To evaluate the efficacy and safety of polyethylene glycol loxenatide (PEX168) monotherapy in type 2 diabetes (T2D) patients in China. Materials and Methods In a multicentred, randomized, double‐blinded, placebo‐controlled phase 3a clinical trial, 361 patients with inadequate glycaemic control (HbA1c 7.0%‐10.5%, fasting plasma glucose <13.9 mmol/L) were randomized (1:1:1) for weekly subcutaneous injections: placebo, PEX168/100 μg or PEX168/200 μg. The 24‐week treatment was followed by a 28‐week extension, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 30 publications
3
35
0
Order By: Relevance
“…However, the GLP-1RAs hypoglycemic mechanism depends on blood glucose levels in patients regulating islet function [ 15 ], so the levels of FBG were returned to normal at the 11th week, and follow-up intervention had a positive effect. In the clinical trials of Shuai et al [ 13 ], T2DM patients' blood glucose levels improved significantly during the treatment of diabetes with PEX-168 and there was no hypoglycemia, which confirmed the safety of PEX-168 regulation of blood glucose in T2DM patients. But, in this study, PEX-168 was used in nondiabetic simple obese mice, and the MD and HD group had hypoglycemia, indicating that, in simple obese mice with normal blood glucose, there is a risk of hypoglycemia, so low doses should be considered as starting quantities.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…However, the GLP-1RAs hypoglycemic mechanism depends on blood glucose levels in patients regulating islet function [ 15 ], so the levels of FBG were returned to normal at the 11th week, and follow-up intervention had a positive effect. In the clinical trials of Shuai et al [ 13 ], T2DM patients' blood glucose levels improved significantly during the treatment of diabetes with PEX-168 and there was no hypoglycemia, which confirmed the safety of PEX-168 regulation of blood glucose in T2DM patients. But, in this study, PEX-168 was used in nondiabetic simple obese mice, and the MD and HD group had hypoglycemia, indicating that, in simple obese mice with normal blood glucose, there is a risk of hypoglycemia, so low doses should be considered as starting quantities.…”
Section: Discussionmentioning
confidence: 82%
“…Since there are limited drugs to treat obesity patients and GLP-1RAs have the effect on reducing body weight, it is necessary to study the effect of PEX-168 on weight and blood glucose in simple obesity patients, which can provide relevant data reference for weight loss field. A number of studies have confirmed the safety and efficacy of PEX-168 in patients with T2DM [ 9 , 13 ], while whether PEX-168 can bring a weight loss effect in patients with simple obesity under normal control of blood glucose has not been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 ] In diabetes, a polyethylene glycol loxenatide (PEX168) is a novel once‐weekly subcutaneously administered GLP‐1 receptor antagonist which has successfully demonstrated significantly improved glycaemic control in Type II Diabetes patients in a Phase IIIa trial. [ 19 ] Local delivery for early disease and pre‐malignant disease is growing in importance as early detection and diagnostic approaches improve, polymer therapeutics play an important role as delivery systems for many easily assessable sites such as brain, peritoneum, bladder, and eye where the physiological barriers to accessing tumors are reduced. Whatever the indication, a disease led approach is required and a full pathophysiological understanding of the disease biology, the drug and its target, and the polymer therapeutic is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…However, research in Jessica and Tina pointed out that further research is still needed to determine the effect of GLP-1 receptor agonists in overweight or obese patients without type 2 diabetes [ 11 , 12 ]. Studies have proven the efficacy and safety of PEX-168 in the treatment of patients with T2DM [ 13 , 14 ], but the effect of PEX-168 on simple obesity and on the regulation of chemerin and omentin expression has not been reported. This study therefore selected six indicators to evaluate the effect of PEX-168 according to prior research and the drug characteristics.…”
Section: Introductionmentioning
confidence: 99%